2022
DOI: 10.1093/jncics/pkac001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Germline Genetic Testing in Japanese Men Undergoing Prostate Biopsy

Abstract: Background Multiple common variants and also rare variants in monogenic risk genes such as BRCA2 and HOXB13 have been reported to be associated with risk of prostate cancer (PCa); however, the clinical setting in which germline genetic testing could be utilized for PCa diagnosis remains obscure. Herein, we tested the clinical utility of a 16 common-variant based polygenic risk score (PRS) that have been developed previously for Japanese, and also evaluated the frequency of PCa associated rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…25,27,28 More recently, SNPs have been incorporated into prediction algorithms in post-PSA setting. 16,17,[29][30][31][32][33] The Stockholm3 (STHLM3) test, which combines clinical variables, five plasma protein markers, and a GRS derived from 101 PCa susceptibility SNPs, has been shown to reduce the number of performed prostate biopsies while maintaining sensitivity for clinically significant diseases in European descendants. 17,[29][30][31][32][33] However, there has been no prior report using SNPs to enhance the prediction of PCa risk for biopsy referral in AA men with elevated PSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,27,28 More recently, SNPs have been incorporated into prediction algorithms in post-PSA setting. 16,17,[29][30][31][32][33] The Stockholm3 (STHLM3) test, which combines clinical variables, five plasma protein markers, and a GRS derived from 101 PCa susceptibility SNPs, has been shown to reduce the number of performed prostate biopsies while maintaining sensitivity for clinically significant diseases in European descendants. 17,[29][30][31][32][33] However, there has been no prior report using SNPs to enhance the prediction of PCa risk for biopsy referral in AA men with elevated PSA.…”
Section: Discussionmentioning
confidence: 99%
“…While considerable efforts have been directed towards the first application, [11][12][13][14][15] limited research has focused on assessing the utility of these SNPs in the post-PSA setting. [16][17][18][19] Notably, research regarding this second application has been particularly scarce in AA men.…”
Section: Introductionmentioning
confidence: 99%
“…When first applied for clinical use in the early 2000s [15], the PRS was conceptualized as a single value, combinatory estimate for an individual's genetic risk for disease using an additive sum of effect size estimated from GWAS summary statistics. Previous studies have described the potential clinical use of PRS for cancer and other common diseases, which range from risk prediction, informing decision-making during screening, guiding prevention strategies, and assisting personal understanding of individual lifetime risk [11,16,17 ▪▪ ,18 ▪▪ ].…”
Section: Polygenic Risk Scoresmentioning
confidence: 99%
“…Our previous study also suggested that PRS could significantly predict the lifetime risk of PCa in the Chinese population [ 7 ]. It may also significantly and independently predict prostate biopsy outcomes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation between PRS and PSA for predicting PCa was reported in different studies with different populations including European [ 13 , 14 ], Finnish [ 15 , 16 ], Japanese [ 8 ], and Chinese [ 17 ]. Studies also investigated the combined effect of PRS and the novel approaches and suggested that PRS could provide significant predictive value for PCa in addition to PCA3, 4K Score, or mpMRI [ 6 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%